Design and real‐time implementation of an adaptive fuzzy sliding mode controller for a coupled tank system. (5th September 2018) - Mahapatro, Soumya Ranjan; Subudhi, Bidyadhar; Ghosh, Subhojit
Abstract: In this paper, an adaptive fuzzy sliding mode controller (AFSMC) is proposed for regulation of liquid level in a coupled tank system (CTS). In this controller design, a fuzzy variable is considered in the sliding surface in order to reduce the chattering effect. The proposed controller exhibits high robustness against external disturbances and also measurement error. To verify the efficacy of the proposed controller, we compared its performances with that of a linear matrix inequality (LMI)–based proportional integral (PI) controller. The efficacy of the proposed controller is verified by implementing this controller in real time on the coupled tank liquid level system. From both the obtained simulation and experimental results, it is observed that the proposed controller exhibits superior control performance to maintain the desired level as compared with the LMI‐based PI controller.